2013
DOI: 10.1108/ejm-10-2011-0568
|View full text |Cite
|
Sign up to set email alerts
|

Is social norms marketing effective?

Abstract: Purpose -The purpose of this paper is to present details of a large-scale experiment that evaluated the impact of communicating two types of feedback to householders regarding their domestic electricity consumption: feedback on their own consumption and feedback of both their own consumption and that of others in their locality. Design/methodology/approach -Digital technologies were used to automatically measure and communicate the electricity consumption of 316 UK residents for a period of 16 weeks. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…An alternative interpretation, however, is that this finding indicates issues with the design of the social feedback used. Practitioners of the social norms approach argue that the most effective reference group consists of those that participants consider most like themselves [23, 46, 47]. Although all participants were of the same gender and of approximately the same age, the social feedback might have been more effective if the age-band had been narrower or if a distinction had been made between, for example, those in physically active occupations and those doing more sedentary work.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative interpretation, however, is that this finding indicates issues with the design of the social feedback used. Practitioners of the social norms approach argue that the most effective reference group consists of those that participants consider most like themselves [23, 46, 47]. Although all participants were of the same gender and of approximately the same age, the social feedback might have been more effective if the age-band had been narrower or if a distinction had been made between, for example, those in physically active occupations and those doing more sedentary work.…”
Section: Discussionmentioning
confidence: 99%
“…Miller & Prentice, 2016). The fact that participants were aware that the presented information was part of a scientific inquiry might have contributed further to lowering the level of perceived trustworthiness (see also Harries, Rettie, Studley, Burchell, & Chambers, 2013). Whereas this offers an explanation for why exposure to social comparison feedback may fail to produce the desired results, it does not account for the differences found across the two studies.…”
mentioning
confidence: 99%
“…This was not the case in the study by Toner et al (2014), in which the feedback was provided individually whilst participants sat in front of a computer. Furthermore, research has shown that people become more engaged in seeking information about their current consumption patterns when individual feedback is combined with group feedback, compared with when they receive only the former (Harries et al, 2013).…”
mentioning
confidence: 99%
“…Without rejecting the idea that perceived efficacy may help to explain feedback effects in some contexts, there is room to consider alternative explanations. Other mechanisms that could account (at least partly) for the effects of norm-based interventions are that they induce negative emotions such as guilt or shame, particularly in public settings [45], or that they stimulate information-seeking behaviour [48].…”
Section: Discussionmentioning
confidence: 99%